Self-disorders in individuals with attenuated psychotic symptoms: Contribution of a dysfunction of autobiographical memory. (30th May 2016) - Berna, Fabrice; Göritz, Anja S.; Schröder, Johanna; Martin, Brice; Cermolacce, Michel; Allé, Mélissa C.; Danion, Jean-Marie; Cuervo-Lombard, Christine V.; Moritz, Steffen
Abstract: Patients with schizophrenia and people with subclinical psychotic symptoms have difficulties getting a clear and stable representation of their self. The cognitive mechanisms involved in this reduced clarity of self-concept remain poorly understood. The present study examined whether an altered way of thinking or reasoning about one's past may account for the reduced clarity of self-concept in individuals with attenuated psychotic symptoms (APS). An online study comprising 667 participants examined the capacity to give a meaning to past events and to scrutinize autobiographical memory to better understand him/herself. Our results showed that in this sample, individuals with APS ( n =49) have a lower clarity of self-concept and a higher tendency to scrutinize autobiographical memory than controls subjects ( n =147). A mediation analysis performed on the full sample revealed that the relation between APS and clarity of self-concept was mediated by a tendency to scrutinize autobiographical memory. Our results suggest that the weakness of self-concept, which increases with the intensity of psychotic symptoms, may be related to an altered function of autobiographical memory, so that examining past events may fail to sustain a stable and clear representation of the self when psychotic symptoms increase. Highlights: Attenuated Psychotic Symptoms (APS) are associated with lower clarity of self. APS enhance the tendency to scrutinize one's past for self-understanding. The self-continuity function of autobiographical memory is deficient in APS. Meaning making is not reduced in individuals with high APS.